2015
DOI: 10.1186/s13046-014-0119-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the ORFK1 hypervariable regions reveal distinct HHV-8 clustering in Kaposi’s sarcoma and non-Kaposi’s cases

Abstract: BackgroundClassical Kaposi’s Sarcoma (cKS) is a rare vascular tumor, which develops in subjects infected with Human Herpesvirus-8 (HHV-8). Beside the host predisposing factors, viral genetic variants might possibly be related to disease development. The aim of this study was to identify HHV-8 variants in patients with cKS or in HHV-8 infected subjects either asymptomatic or with cKS-unrelated cutaneous lymphoproliferative disorders.MethodsThe VR1 and VR2 regions of the ORF K1 sequence were analyzed in samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 65 publications
2
100
0
1
Order By: Relevance
“…Investigation of biomarkers potentially useful for KS prognosis based on different loci of genome [9,10,12,14,15,18] or whole-genome data [16] has advanced parallel to the molecular characterization of a large number of HHV-8 strains infecting patients from different clinical and epidemiological forms of KS. [9,10,12,14,15] For example, several short targets of HHV-8 from AIDS-KS lesions were selected to identify distinctive molecular pattern, but with restricted coverage of the repertoire of HHV-8 genotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of biomarkers potentially useful for KS prognosis based on different loci of genome [9,10,12,14,15,18] or whole-genome data [16] has advanced parallel to the molecular characterization of a large number of HHV-8 strains infecting patients from different clinical and epidemiological forms of KS. [9,10,12,14,15] For example, several short targets of HHV-8 from AIDS-KS lesions were selected to identify distinctive molecular pattern, but with restricted coverage of the repertoire of HHV-8 genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10,12,14,15] For example, several short targets of HHV-8 from AIDS-KS lesions were selected to identify distinctive molecular pattern, but with restricted coverage of the repertoire of HHV-8 genotypes. [1719,12,2023] Nowadays, sequence analysis of highly variable ORF K1 regions (i.e., VR1 and VR2) has allowed the identification of 7 major subtypes or genotypes of HHV-8 (A, B, C, D, E, F, and Z), all exhibiting clear ethnic and geographic clustering.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical relevance of piRNAs was first apparent when they were reported to be associated with clinicopathological factors such as lymph node status [23], and TNM stage [24]. Nonetheless, our understanding of their contribution as prognostic markers is rudimentary and warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the differential expression of piRNAs and therefore their oncogenic or tumor suppressor roles have also been observed in various cancer types [19, 20], and a few studies have highlighted their association with clinicopathological factors [23]. An even smaller number of studies have reported the relevance of piRNAs as prognostic/diagnostic markers [2426]; however, the study designs of the majority of these studies are limited to candidate piRNA molecules or are challenged with limited sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…As lncRNAs do not code for proteins, lncRNA expression may be a better indicator of the tumor status, implying the potential and superiority as independent biomarkers for early diagnosis and prognosis prediction in cancers [29]. Currently, several expression-based lncRNA signature have been identified to predict patients' survival in some cancers, including glioblastoma multiforme [30], oesophageal squamous cell carcinoma [31], colorectal cancer [32], breast cancer [3335], lung cancer [36] and multiple myeloma [37]. Recent studies have revealed that changes in lncRNA expression were associated with OvCa tumorigenesis and metastasis.…”
Section: Introductionmentioning
confidence: 99%